SCAFFOLDING STRATEGIES USED BY THE EXPERIENCED AND NOVICE ENGLISH TEACHERS - Nur Intan Asmara, - (2018)
This study aims to find out the types of scaffolding strategies used by the experienced and the novice English teachers and to know how the scaffolding strategies used by the experienced and the novice English teacher influence the students' improvement in learning English. This qualitative study was conducted in a public junior high school in Bandung. An experienced and a novice English teachers were involved in this study. The data in this study were collected through observation, interview and document analysis. This study employs case study as the design of this research. In analyzing the data, the classroom activity was recorded, transcribed and coded to find out the types of scaffolding strategies used by the teachers. Interviewing the teacher and the students, analyzing the teachers/ students documents were also conducted to support the data and also to know the influences of the strategies used to the students' improvement in learning English. The result shows that there are several types of scaffolding strategies used by the experienced teacher: setting and sharing the goal to the students, considering the appropriateness of the tasks, sequencing the task, verifying and clarifying students' understanding, offering ex planation, providing hints, modelling, inviting students' participation and contextualizing. The novice English teacher also used several types of the scaffolding strategies: set and share the goal of the study, offering explanation, providing hints, modelling, verifying and clarifying students' understanding, inviting students' participation and contextualizing. In the Experienced teacher's class, it was found that the students' knowledge in developing a descriptive text improved through verifying/ clarifying students' understanding strategy. In the novice teacher's class, it was found that the students' knowledge about descriptive text improved through offering explanation strategy.----Penelitian ini bertujuan untuk melihat jenis-jenis strategi scaffolding yang digunakan oleh guru Bahasa Inggris berpengalaman dan guru Bahasa inggris pemula serta mencari tahu bagaimana strategi scaffolding yang diimplementasikan oleh kedua guru tersebut mempengaruhi pencapaian siswa dalam belajar Bahasa Inggris. Penelitian yang menggunakan pendekatan kualitatif ini dilakukan di salah satu Sekolah Menengah Pertama (SMP) di Bandung. Subjek penelitian dari studi ini adalah seorang guru Bahasa Inggris berpengalaman dan seorang guru Bahasa inggris pemula. Data dalam penelitian ini dikumpulkan melalui observasi, wawancara serta dokumen-dokumen. Penelitian ini menggunakan desain case study. Dalam menganalisa data, penelitian ini pertama merekam aktifitas didalam kelas, mentranskripsi serta melabeli data untuk mencari tahu jenis strategi scaffolding yang dipakai oleh guru. Selain itu, hasil wawancara serta dokumen-dokumen dikumpulkan untuk mengetahui pengaruh strategi-strategi scaffolding yang dipakai oleh guru terhadap pencapaian siswa dalam pembelajaran Bahasa Inggris. Hasil penelitian menunjukan bahwa terdapat beberapa jenis strategi scaffolding yang dipakai oleh guru berpengalaman didalam kelas diantaranya membentuk serta menjelaskan tujuan pembelajaran kepada siswa, mempertimbangkan kesesuaian tugas, menyusun atau mengurutkan tugas, meverifikasi dan mengklarifikasi pemahaman siswa, memberikan penjelasan, memberikan petunjuk, melakukan pemodelan, mengajak siswa untuk berpartisipasi, dan mengkontekstualisasikan pembelajaran. Sementara itu, strategi scaffolding yang dipakai oleh guru Bahasa Inggris pemula adalah diantaranya membentuk serta menjelaskan tujuan pembelajaran kepada siswa, memberikan penjelasan, memberikan petunjuk, melakukan pemodelan, mengajak siswa untuk berpartisipasi, dan mengkontekstualisasikan pembelajaran. Di kelas guru yang berpengalaman, ditemukan bahwa pengetahuan siswa didalam mengembangkan teks dekriptif meningkat dengan bantuan strategi verifikasi dan klarifikasi pemahaman siswa. Sedangkan di kelas guru pemula kemampuan siswa dalam mengembangkan teks deskriptif itu meningkat dengan cara menggunakan strategi memberikan penjelasan.